The economic impact of foot and mouth disease and its control in South-East Asia: A preliminary assessment with special reference to Thailand - Perry, Brian D.; Kalpravidh, W.; Coleman, P.G.; Horst, H.S.; McDermott, John J.; Randolph, Thomas F.; Glesson, L.J. (World Organisation for Animal Health, 1999)
A pilot study of the economic impact of foot and mouth disease (FMD) in the countries and region of South-East Asia is described. Previous economic impact assessments are reviewed and summarised and a synthesis of these contributions is constructed. A framework for the future economic impact of the disease is then developed, incorporating analyses at the sectorl (production system), national and regional levels. Data requirements for such studies are also identified. Integrated epidemiological and economic models for impact assessment were developed and applied to the case study country of Thailand. The models were used to evaluate the economic viability of FMD control programmes in the country. Scenarios evaluated include the effect of improving vaccination coverage and thus reducing productivity losses, and the effect of eventual eradication of the disease. The results indicate that economic returns to the high expenditures incurred in FMD control could be achieved in the shorterm if greater international trade in pork products was made possible and export prices higher than those in the domestic market could be attained. If FMD were to be eradicated from Thailand in 2010, the eradication would be economically viable, even without exports, with a predicted benefit-cost ratio of 3.73. With additional exports, the economic justification for control becomes much stronger with a benefit-cost ratio of up to 15.1 being achieved. If eradication is not achieved until 2020, returns remain positive without exports, but at a lower rate. The authors propose that the integrated epidemiological and economic models developed be applied to other countries of the region to gain a more accurate insight into the future benefits of FMD control and eradication in the region.